Prevalence and associated factors for carriage of Enterobacteriaceae producing ESBLs or carbapenemase and methicillin-resistant Staphylococcus aureus in Hong Kong community. Issue 2 (August 2020) - Kwok, Kin-On; Chan, Emily; Chung, Pui-Hong; Tang, Arthur; Wei, Wan-In; Zhu, Chendi; Riley, Steven; Ip, Margaret
Highlights: Abundance of ESBL-E in Hong Kong community are causes of concern. Antibiotic use is associated with ESBL-E carriage. Presence of MRSA and CPE in the community hints on a change in their epidemiology. Abstract: Objectives: We conducted a cross-sectional study in Hong Kong community to estimate the carriage prevalence, associated factors and genotypes of extended-spectrum beta-lactamase producing Enterobacteriaceae (ESBL-E), methicillin-resistant Staphylococcus aureus (MRSA) and carbapenemase-producing Enterobacteriaceae (CPE). Methods: Seemingly healthy subjects were asked to provide nasal, handprint and stool samples from March to April 2017. Isolates were characterized by molecular methods. We used multivariable logistic regression models within a generalized estimating equation framework to identify risk factors for ESBL-E carriage. Characteristics of MRSA/CPE carriage were summarized. Results: The prevalence of ESBL-E, MRSA and CPE were 52.8% (104/197), 2.5% (5/197) and 0.5% (1/197) respectively. Most ESBL-E isolates were E. coli (85.6%; 113/132). Most ESBL genes belonged to bla CTX−M-G9 (68.9%) and bla TEM (53.0%) types. Self-reported antibiotic consumption (≥2 courses) in the past six months was associated with ESBL-E carriage (adjusted odds ratio: 4.71–5.47). Conclusions: Abundance of ESBL-E in the community are causes of concern, and antibiotic use is associated with its carriage. Presence of MRSA and CPE in community members without clear healthcare exposure hints on a change in their epidemiology. This study establishes a baseline to formulate infection control policies and future studies in combating antimicrobial resistance.